Initiation Stories: An Examination of the Narratives of People Who Assist With a First Injection. (10th November 2015) - Kolla, Gillian; Strike, Carol; Roy, Élise; Altenberg, Jason; Balian, Raffi; Silver, Rey; Hunt, Neil
Abstract : Background: Research in the area of initiation to injection drug use that focuses on the perspective of initiators, or those who help with a first injection, is rare. Objective: To explore the process of initiation to injection drug use from the point of view of initiators. Methods: Semi-structured, in-depth qualitative interviews were conducted at a harm reduction program in Toronto, Canada. Twenty participants who had injected drugs in the last 30 days and who reported ever having initiated another person to injection drug use were recruited. A narrative analytic approach was used to explore the spectrum of narratives surrounding their experiences initiating others to injection drug use. Results: Initiation events arise in a complex interplay of individual circumstances and social contexts. People who inject may assist with a first injection for a variety of reasons, from conceding to social pressure, to wanting to help reduce a perceived risk of harm, to assisting because it provides a sense of pride at possessing a skill or of having helped someone achieve a desired state, to assisting to obtain drugs or to cope with withdrawal, or a mix of several of these reasons at once. Conclusions/Importance: Narratives reveal that preventing all instances of initiation is unrealistic. Combining elements from existing interventions that focus on enhancing reluctance to assist with initiation with safer injection training has the potential to reduce initiations and perhaps reduce injection related harm for novices if initiation occurs.